2005
DOI: 10.1016/j.jtcvs.2005.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Surgical results for bronchiectasis based on hemodynamic (functional and morphologic) classification

Abstract: The hemodynamic (functional and morphologic) classification provides an accurate functional classification for bronchiectasis. Its application in determining the indications and extent of surgical resection is superior to morphologic classification alone. Curative resection can be achieved in both unilateral and bilateral bronchiectasis with acceptable morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…Besides medical treatment and respiratory physiotherapy, surgical treatment is an eligible therapy for patients with non-CF bronchiectasis, especially to those with little response to conservative interventions 7 . Over the years, many studies have reported surgical intervention in the management of patients with non-CF bronchiectasis 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 . The surgical procedure was aimed at primary resection of the affected area, as assessed by high-resolution computed tomographic (HRCT).…”
mentioning
confidence: 99%
“…Besides medical treatment and respiratory physiotherapy, surgical treatment is an eligible therapy for patients with non-CF bronchiectasis, especially to those with little response to conservative interventions 7 . Over the years, many studies have reported surgical intervention in the management of patients with non-CF bronchiectasis 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 . The surgical procedure was aimed at primary resection of the affected area, as assessed by high-resolution computed tomographic (HRCT).…”
mentioning
confidence: 99%
“…2 For partial resection for nonlocalized bronchiectasis, the basic principle of the operation is to resect as little lung as one can (eg, lobectomy and segmentectomy, rather than pneumonectomy) in a palliative manner. 28 All patients had less than 50% bronchiectatic lung after lobectomy, which implies that at least half healthy lung should remain in nonlocalized bronchiectasis when surgery is considered. This should be interpreted with caution, however, because of the small number of patients included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Konservatif tedavi uygulanır. Çoğunluğunu kistik fibrozisli hastaların oluşturduğu seçilmiş olgularda ise kombine kalp-akciğer veya çift akciğer transplantasyonu yapılabilir (14). Günümüzde bronşektazide cerrahi tedavi; kabul edilebilir 8-24,6% morbidite ve 0-2,2% mortalite oranları ile uygulanmaktadır (3,8).…”
Section: Discussionunclassified